Case report: A simple and reliable approach for progressive internal distraction of the sternum for Jeune syndrome (asphyxiating thoracic dystrophy): preliminary experience and literature review of surgical techniques - Inserra, Alessandro; Zarfati, Angelo; Pardi, Valerio; Bertocchini, Arianna; Accinni, Antonella; Aloi, Ivan Pietro; Martucci, Cristina; Frediani, Simone (Frontiers in Pediatrics, 2023)
Background Described for the first time in 1954, Jeune syndrome (JS), often called asphyxiating thoracic dystrophy, is a congenital musculoskeletal disease characterized by short ribs, a narrow thorax, and small limbs. In this study, we analyzed and presented our preliminary experience with a device for progressive internal distraction of the sternum (PIDS) in patients with symptomatic JS. In addition, we reviewed the contemporary English literature on existing surgical techniques for treating children with congenital JS. Material and methods A retrospective analysis of pediatric patients (<18 years old) treated for symptomatic JS at our tertiary center between 2017 and 2023 was performed. Results We presented two patients with JS who underwent surgery using an internal sternal distractor, a Zurich II Micro Zurich Modular Distractor, placed at the corpus of the sternum among the divided halves. Conclusions We obtained promising results regarding the safety and effectiveness of this less-invasive device for PIDS in patients with symptomatic JS. Further studies on long-term outcomes are needed to validate these findings.